2013
DOI: 10.1111/anae.12486
|View full text |Cite
|
Sign up to set email alerts
|

Accidental spinal potassium chloride injection successfully treated with spinal lavage

Abstract: Summary We describe the management of a 62‐year‐old man who developed severe pain, cramps, paraplegia and pulmonary oedema after the accidental administration of potassium chloride into the subarachnoid space. In addition to supportive treatment, we performed cerebrospinal fluid lavage with saline 0.9%. The patient recovered well without any permanent injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Sixty minutes after commencing the infusion, the dye in the "Slow A60'" experiment was completely eliminated while in the "Fast B60'" bag, a small amount of staining was still present mized by the directionality of intrathecally administered hyperbaric local anesthetic solutions. 18 Maldistribution has previously featured in anesthesia related problems, being blamed for local anesthetic neurotoxicity. 42,43 Purposeful mixing largely eliminates solute maldistribution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixty minutes after commencing the infusion, the dye in the "Slow A60'" experiment was completely eliminated while in the "Fast B60'" bag, a small amount of staining was still present mized by the directionality of intrathecally administered hyperbaric local anesthetic solutions. 18 Maldistribution has previously featured in anesthesia related problems, being blamed for local anesthetic neurotoxicity. 42,43 Purposeful mixing largely eliminates solute maldistribution.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Recently, ampoule similarity resulted in accidental subarachnoid injection of concentrated potassium instead of bupivacaine. 18 Typical safety guidelines have included the removal of concentrated potassium ampoules from clinical areas and storage only within certain locations (pharmacy, Intensive Care Units and operating rooms), storage within a locked cupboard as for controlled substances, supplying premixed potassium containing bags, using easily distinguishable packaging and labels for bags and ampoules, specifying onsite preparation protocols, and administration using volumetric pumps. 9,11,17,19,20 It has been argued that while safety guidelines to ensure potassium administration errors "never occur again" are logical, 21 they are not backed by objective evidence of efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, the National Patient Safety Agency recommended the supply and use of ready-to-administer, prefilled syringes of fast acting insulin [2]. In 2015, the NHS England Revised Never Events Policy and Framework [3] advised that the availability and use in all clinical areas of ready-to-administer, injectable medicinal products provided a strong, systemic, barrier against preventable patient harm due to…”
Section: Prefilled Insulin Syringesmentioning
confidence: 99%
“…This places patients at continuing risk of drug error, as has been repeatedly highlighted in recent letters to Anaesthesia [2][3][4]. An audit at my Trust recently found that not one drug storage cupboard contained stock that completely adhered to the colour coding for syringe labels there was variation between packaging for the same drug, and in some cupboards, the same drug was stored in at least two different coloured packages and ampoules.…”
mentioning
confidence: 99%
“…Rai's recent editorial in Anaesthesia [1] acknowledges the utility of bougies for videolaryngoscopic intubations.…”
mentioning
confidence: 99%